Sistem Pendukung Keputusan Pemberian Penghargaan Berdasarkan Prestasi Berbasis Web Dengan Metode Promethee - senopati, handaru (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
Award is an achievement given to individuals or groups. Awarding is useful to increase students' enthusiasm so they can continue to develop themselves and their achievements. The awarding so far is still conventional, starting from data collection to determining results. This study aims to assist in decision-making decisions. The research method used is the waterfall system development method which consists of analysis, interface design, implementation and testing. The results of the above research are in the form of a decision support system which can later become a reference for selecting candidates who are entitled to receive awards.